STUDI KEPUASAN KONSUMEN PRODUK KERIPIK TALAS UD SELALU JAYA DI KOTA MATARAM - Ni Putu Febri Listanaya Pratami; Tajidan Tajidan; I Wayan Suadnya (JURNAL AGRIMANSION, 2021)
The purposes of this research are to 1) determine the level of consumer satisfaction with taro chips products at UD Selalu Jaya in Mataram City, 2) find out what are the attributes of taro chips that determine customer satisfaction, 3) determine the relationship between product quality and customer satisfaction levels of taro chips.The method used in this research is descriptive method and data collection techniques using a questionnaire / questionnaire and observation. This research was conducted in Mataram City by determining three districts, namely Mataram District, Selaparang District and Cakranegara District. Determination of respondents was determined by as many as 50 respondents, the type of data used was quantitative and qualitative data, while the data source used was primary data. The data obtained were analyzed by 1) Validity and Reliability Test, 2) Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI).The results of the study said that 1) the level of customer satisfaction with the UD Selalu Jaya taro chips product in the city of Mataram using the calculation of the Customer Satisfaction Index (CSI) shows that all consumers are quite satisfied, this can be seen from the CSI value of 0.64 with a scale range. 0.51-0.65.) The relationship between product quality and the level of consumer satisfaction, the relationship shows a positive linearity relationship, namely the higher the product performance, the higher the level of consumer satisfaction. Attributes that need to be prioritized to be improved are product quality, shape, color and aroma.